FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN EMISI GAS RUMAH KACA DARI PERSPEKTIF AKUNTANSI HIJAU - Deantari, Sri Anggita Olvin; Pinasti, Margani; Herwiyanti, Eliada (EQUILIBRIUM, 2019)
This study aims to analyze the effect of environmental management system, environmental performance, size, profitability and leverage to greenhouse gas emissions disclosure in Indonesia companies. To measure the extent of carbon emission disclosure used checklist that was developed based on the information request sheets provided by the carbon disclosure project (CDP). The population of this study was all basic industrial and chemical companies listed on the Indonesia Stock Exchange during 2014-2016. Sampling method used in this research is purposive sampling method so that obtained samples based on the criteria as many as 60 research samples. Type of data used is secondary data. Data analysis used descriptive statistic, Classical Assumption Test, Multiple Linear Regression Analysis, Goodness of Fit Test, Coefficient of Determination Analysis (R²) and Hypothesis Testing (t test). The results of 5 hypothesis, 4 hypothesis accepted and 1 hypothesis rejected. Variable Environmental Management System, Environmental Performance and Size have positive and significant and Leverage have negative and significant impact to carbon emission disclosure. While profitability have positive but not significant impact in basic industrial and chemical companies in Indonesia. Based on Adjusted R Square is seen that the value of coefficient of determination is 0.663, it means that the Greenhouse Gas Emission Disclosure can be explained by independent variable equal to 66,3% and 33,7% explained by other variable.